Evaluation of national dental curriculum in Iran using senior dental students' feedback - Arvin Salmani; Hooman Keshavarz; Majid Akbari; Mohammad Javad Kharrazifard; Shabnam Varmazyari; Mohammad Reza Khami (BMC, 2023)
Abstract Background Dental curriculums require regular revision to stay up to date in scientifical and societal fields. Senior dental students are among the main stakeholders of such curriculums. The present study investigated the opinions of Iranian senior dental students regarding the adequacy of their dentistry program and the national dental curriculum in training a competent dentist, the program's content, and its structure. Methods A previously designed and validated questionnaire on the opinion of senior dental students regarding curriculum adequacy was sent to a representative in each of the country's dental schools. Before the COVID pandemic terminated data collection, a total of 16 schools (438 students) managed to respond (37%). The questionnaire asked the students to assess the adequacy of the training received in curriculum's theoretical and practical competencies with the help of a five-point Likert scale that ranged from "Completely inadequate" to "Completely adequate". It also questioned them on its teaching methods and intensity. SPSS software version 24 and Chi-square test served for statistical analysis. Results In total, the study has 438 participants, 245 female and 193 male. Significant sex differences were spotted in the responses concerning both theoretical and practical training. Regarding general training adequacy, 50 (22.6%) female students and 50 male ones (30.7%), P = 0.08 agreed that the program was acceptable. The numbers for students of old (more than 15 years of activity) and new schools were 47 (21.7%) and 53 (31.7%), respectively (P = 0.03). Nearly one-third deemed the teaching methods appropriate. Regarding the duration of curriculum phases, 33 students (8.3%) believed that basic science required extension, while 108 (28.6%) and 266 (69.1%) reported such need for pre-clinical and clinical phases. The school's years of activity emerged as significant, as 38.1% of students from new schools versus 21.7% of those from old ones deemed the extension of pre-clinical phase necessary (P < 0.001). Conclusion A significant number of Iranian senior dental students found the undergraduate dental curriculum inadequate regarding competencies, content, and teaching. Further investigations will determine whether it's the curriculum or its implementation that warrants revision.